POPULATION OF MACROZOOBENTOS IN MARIAH BANDAR SPRING WATERS, PEMATANG BANDAR DISTRICT, SIMALUNGUN REGENCY, NORTH SUMATRA - Masdiana Sinambela; Yosepin Hutagaol; Tonggo Sinaga; Andreas Simorangkir (JBIO: jurnal biosains (the journal of biosciences), 2023)
Research on macrozoobenthic populations in Mariah Bandar Springs, Pematang Bandar District, Simalungun Regency, North Sumatra Province was carried out from May 2022 to June 2022. The purpose of this study was to gather information about macrozoobenthos populations in Mariah Bandar Springs and to find out about the diversity of macrozoobenthos populations in Mariah Bandar Spring Waters. This research was conducted in three locations, namely upstream, middle and downstream of Mariah Bandar Springs. There are each sub-location from each of these locations, in one location consisting of the upper, middle and lower ends. Each of the locations uses three points in macrozoobenthos sampling. Macrozoobenthos sampling using surber net. The results showed that there were 9 species of macrozoobenthos including Lumbricus sp, Thiara winteri, Enallagma nymph, Thiara scraba, Corbicula fluminea, Chironomus sp, Orthetrum glaucum larvae, Hagenius brevistylus and Euplanaria sp. Based on the Shannon-Wienner diversity index, locations I, II, III have low diversity (H' = 0.147).